Students' Attitudes towards Teachers' Written Corrective Feedback on Writing Case of Study First Year Master's degree Students of English at University of Mohammed Cherif Messaadia, Souk-Ahras - BRAHMIA Soundous Rayen (My University, 2022)
Abstract Students' attitudes involve their beliefs and preferences towards learning behaviors that considerably influence their learning motivation, and consequently, their success in learning. Therefore, the current study aims to investigate the different attitudes students hold towards teachers' written corrections on their writing. To test our hypotheses that suggest that students will positively perceive their teachers' written corrective feedback if it meets their learning needs and expectation and that will directly affect their writing skill, a questionnaire was administered to first year Master's degree students at the Department of English in Mohammed Cherif Messaadia University in Souk-Ahras. The obtained results reveal that students' positively perceive their teachers' written corrective feedback on their drafts and they believe that it is an effective tool to enhance their writing skill.